B cells in multiple sclerosis. (2nd January 2017) - Wekerle, Hartmut
Abstract: B lymphocytes have essential roles in the autoimmune pathogenesis of multiple sclerosis (MS). They regulate the autoimmune response and participate in the development of the CNS lesions. This review discusses nature and functions of B cells in MS, and retraces the recruitment of brain-autoimmune B cells from the B cell repertoire. Multiple sclerosis is commonly considered as an autoimmune demyelinating disease, where myelin-reactive T cells enter the CNS from outside, and drive the inflammatory changes that ultimately create the degenerative MS plaque. Most therapeutic strategies focus on eliminating or mitigating these pathogenic T cells. Less consideration has been devoted to the role of autoimmune B cells in the autoimmune pathogenesis. Indeed, this role is now supported by a number of convergent lines of evidence, which are briefly outlined in a first part of this overview. A second part describes experimental studies in transgenic mouse models of brain autoimmunity, EAE, which relate to possible functions of autoimmune B cells and to their recruitment from the regular B cell repertoire.